Positive Implicative Makgeolli Ideals of BCK-algebras (European Journal of Pure and Applied Mathematics, 2022)
The concept of a positive implicative makgeolli ideal in BCK-algebras is introduced, and its properties are investigated. The relationship between a makgeolli ideal and a positive implicative makgeolli ideal is established. The conditions under which a makgeolli ideal can be a positive implicative makgeolli ideal are explored. Characterizations of a positive implicative makgeolli ideal are discussed, and the extension property for a positive implicative makgeolli ideal is established.
Keywords: BCK-soft universe; makgeolli structure; makgeolli ideal; positive implicative makgeolli ideal